Correlation between the number of oocytes and the increase of polyspermy rate in IVF cycles - Yating Sun; Aizhen Zhu (Taylor & Francis Group, 2023)
Aims: To investigate the association between the number of oocytes and the polyspermy rate following in vitro fertilization (IVF) treatment. Materials and methods: 376 IVF cycles with gonadotropin-releasing hormone (GnRH) antagonist protocol in the reproductive center of our hospital were retrospectively included in the analysis, which were divided into five groups according to the number of oocytes retrieved. Group A (78 cases):1-5 oocytes, group B (118 cases): 6-10 oocytes, group C (94 cases): 11-15 oocytes, group D (55 cases): 16-20 oocytes, group E (31 cases): ≥21 oocytes. According to polyspermy rate, 376 IVF cycles were then divided into two groups. Normal level polyspermy group (170 cases): polyspermy rate<6%, and high level polyspermy group (206 cases): polyspermy rate ≥ 6%. The variables with p < .10 in univariate analysis were incorporated into the multiple logistic regression model to control the confounding, and the effect of the number of oocytes on the increase of polyspermy rate was analyzed. Results: Multiple logistic regression analysis showed that after adjustment for confounding factor, the increase risk of polyspermy rate in group B, C, D and E was 1.763, 3.804, 2.021 and 3.208 times of that in group A respectively (OR = 1.763, p = .085; OR = 3.804, p = .001; OR = 2.021, p = .158; OR = 3.208, p = .068, respectively). Conclusion: This result demonstrated that when the oocyte number is 15 or less, the more the oocyte number, the greater the increase risk of polyspermy rate. While, there appears to be little increase risk of polyspermy rate when the oocyte number is more than 15.